2015
DOI: 10.3390/f6010252
|View full text |Cite
|
Sign up to set email alerts
|

Combining Lidar and Synthetic Aperture Radar Data to Estimate Forest Biomass: Status and Prospects

Abstract: Abstract:Research activities combining lidar and radar remote sensing have increased in recent years. The main focus in combining lidar-radar forest remote sensing has been on the retrieval of the aboveground biomass (AGB), which is a primary variable related to carbon cycle in land ecosystems, and has therefore been identified as an essential climate variable. In this review, we summarize the studies combining lidar and radar in estimating forest AGB. We discuss the complementary use of lidar and radar accord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
54
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(54 citation statements)
references
References 91 publications
0
54
0
Order By: Relevance
“…Furthermore, optical satellite data have limited value for forest biomass estimation, since the reflectance primarily originates from the upper layer of the forest canopy, and the vertical structure is not assessed. In this situation, using Synthetic Aperture Radar (SAR) satellite data might be the most practical option for large-scale forest mapping [7] by being a cost-effective and time-efficient way to obtain regular estimates of forest resources and to provide accurate input for carbon cycle models.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, optical satellite data have limited value for forest biomass estimation, since the reflectance primarily originates from the upper layer of the forest canopy, and the vertical structure is not assessed. In this situation, using Synthetic Aperture Radar (SAR) satellite data might be the most practical option for large-scale forest mapping [7] by being a cost-effective and time-efficient way to obtain regular estimates of forest resources and to provide accurate input for carbon cycle models.…”
Section: Introductionmentioning
confidence: 99%
“…The fusion of SAR and LIDAR has been attempted to improve SAR-based prediction, and it can be promising for large area efforts; a review showed that the main advantage is in the use of an accurate LIDAR digital elevation model for SAR-based AGB prediction or in the upscale of local LIDAR metrics to large areas with SAR data. 31 Combining SAR and optical data has brought accurate AGB predictions in a number of cases because the structural SAR information can be complemented with canopy density, forest type, and foliage-related information collected by optical instruments. [32][33][34][35][36] Even with the increase in new data, fusion techniques, and innovative researches, AGB prediction based on SAR remains a challenging task, as saturation of the signal is common in forests, 37 where the backscatter is influenced by several factors, such as the soil moisture, especially when the vegetation coverage is low; 38 the forest type, the leaf presence with needleleaf forests possibly having the highest saturation level; 39 the seasonal and weather conditions; 40 the canopy roughness; 41 and the SAR signal polarization as well as the incidence angle.…”
Section: Introductionmentioning
confidence: 99%
“…Radar provides another non-invasive technique to study individual tree and forest structures over wide areas. Radar pulses can either penetrate or reflect from foliage, depending on the selected wavelength (Kaasalainen et al, 2015). Most radar applications occur in forestry and are being operated from satellites or airplanes, although more compact and agile systems are being developed for precision forestry above- and below-ground (Feng et al, 2016).…”
Section: Emerging Questions and Barriers In The Mathematical Analysismentioning
confidence: 99%